Two dimensional mixed traffic flow considering the transit traffic - Li Yang; Junhui Hu; Lingjiang Kong (Institute of Advanced Engineering and Science, 2012)
Based on the two-dimension cellular automaton traffic flow model (BML model), a mixed traffic flow model for urban traffic considering the transit traffic is established in this paper by using the Don't block the box rules. We have investigated the influences of the transit traffic ratio, and found that, in most cases, the urban traffic flow exhibited jam phase. Moreover, focusing on the traffic lights cycle, it is found that the average flow has the periodic fluctuation phenomenon, and we have explained this periodical oscillation change under different boundary conditions. The comparison to practical measured data shows that our stimulation results are accordant with the changes of real traffic flow, which confirms the accuracy and rationality of our model. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1627